Pemberdayaan Masyarakat Melalui Restorasi Eks Lahan Sawit Illegal di Aceh Tamiang - Lembong Misbah (JAROW: Journal of Ar-Raniry on Social Work, 2024)
The Aceh Government's policy, especially Aceh Tamiang, to restore former illegal oil palm plantation land into production forest is one of the structured efforts to improve the conservation of damaged forests and provide more benefits to the community. This research aims to see how this restoration land is used for community empowerment. To answer these objectives, researchers used qualitative methods in the data collection process. The results of this research show that the restoration policy implemented by the government in collaboration with many parties has had a positive impact on ecology and environmental balance, then this program has encouraged local communities to change for the better. Apart from that, this program is in line with the concept of community development and empowerment. For this reason, it is hoped that this program will continue to be strengthened and developed in other areas in Aceh